THE EFFECT OF WORK-RELATED SOCIAL MEDIA USE AND PERCEIVED ORGANIZATIONAL SUPPORT ON WORK ENGAGEMENT - Holistika, Defina (Business Management Analysis Journal (BMAJ), 2024)
This study examined how different factors can influence employees' work engagement. Work-related social media use outside working hours can be a paradox with negative implications for work engagement. Perceived organizational support can be a boost that positively impacts work engagement. A cross-sectional survey was conducted on 344 employees across sectors in the greater Jakarta area to test the research hypothesis. The collected data is then processed using the structural equation modeling (SEM) method. The findings in this study indicate that work-related social media use and perceived organizational support are proven to significantly affect work engagement through the mediating role of organizational identification, work-to-family conflict, and family-to-work conflict. The results of this study are expected to be taken into consideration by organizations in formulating policies on setting balanced working hours, maximizing the role of organizational support, and minimizing the potential for work-family conflict so that employees can feel a strong sense of work engagement and maximize their contribution to the organization in the digital era.